Managing marketing strategies and public relations in public universities. Study of the new communication techniques. - Lunguleac Bardasuc, Leila (UMA Editorial, 2022)
This thesis sets to analyse the communication and marketing processes in higher educational public institutes, the peculiarities and effectiveness of the marketing process regarding the use of new technologies and ways to improve it. A comparison between the public superior educational sector in Spain and in Romania is included, after interviewing top communication executives from each analysed university during 2018 and 2020. The qualitative research conducted brings forward ways of improving communication and PR skills for public universities and also a better understanding of the particularities of the newest communication forms in the educational system. Precisely, the research conducted intends to offer some reflections that contribute to better understand these new techniques which are already adopted in the communication process of universities which highlights strategic and tactical aspects of marketing and social media that make it easier to deploy the new ways of communicating.
Gestionando estrategias de marketing y relaciones públicas en universidades públicas. Estudios de las nuevas técnicas de comunicación
Keywords: Universidad de Málaga - Tesis doctorales; Comunicación; Enseñanza superior; Educación comparada; España; Rumania; Marketing en internet; Universidades - Relaciones públicas; Universidades - Marketing; Public superior education; SEO; Communication strategy; Digital marketing; Social media